Палбам: повесть : [для среднего и старшего школьного возраста] / Аркадий Клабуков - Клабуков Аркадий Николаевич (Удмуртия, 1983)
Экземпляры: кр (1983) / Инвентарный номер: 5631 / Авт.знак: К 47 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)6-44